EKSPOSISI TEKS ALKITAB BAGI PENINGKATAN KETERAMPILAN BERKHOTBAH PARA PENATUA GEREJA PUNGUAN KRISTEN BATAK LUMBAN TONGATONGA - Erman Saragih; Arip Surpi Sitompul; Nurelni Limbong; Iwan Setiawan Tarigan; Bernhardt Siburian; Bresman Sihotang; Jihan Panggabean (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Preaching skills are one of the competency requirements of the elders of the Gereja Punguan Kristen Batak (GPKB). However, based on the results of observations and discussions with the pastor in charge of GPKB Lumban Tongatonga, the problems and obstacles that occur are aspects of elder competence in digging into the Bible and communicative preaching skills that are still not optimal. The image of church elders is, of course, they are seen by the congregation as people who have the competence and can support the development of church ministry through the sermons they deliver. As a GPKB partner institution, the Program Studi Teologi was moved to provide ways to explore Bible texts in improving expository preaching skills for the "elders" of GPKB district V North Tapanuli. The selection of expository text-extracting models is an effort to answer elders' problems in preparing engaging and communicative sermons. The training is carried out on an ongoing basis (kaizen) at the request of the "elders" through the local priest. In the early stages, the theology study program (through homiletics lecturers) delivered expository sermon material and personality criteria with a mini-seminar (interactive) hybrid pattern. Second, practice how to read and explore the meaning of Bible texts. Third, exercises for making “little staples”, outlines, and sermon titles. Fourth, practice outlining and practice expository sermons. The training activity sessions always involve permanent lecturers from the Theology study program (lecturers of the Old and New Testament Bibles). Lecturers function as facilitators. Based on the evaluation form (posttest), "elders" thought that they were helped in terms of how to explore and find the meaning of messages in the text, messages behind the text, and messages in front of the text to be constructed as messages "today" in the form of expository sermon outlines. From this service activity, it was concluded that the elders were increasingly confident in preaching at the GPKB service because they had the understanding and skills to build an expository sermon framework